PERSPEKTIF KARYAWAN TERHADAP NILAI DASAR ISTAWA DI RUMAH SAKIT MUHAMMADIYAH LAMONGAN - Nuriyati Nuriyati (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2018)
Human resources are the most important part of the hospital. Lamongan Muhammadiyah Hospital makes an organizational culture which called ISTAWA as the foundation of employees in serving patients. This study aims to determine the level of knowledge and understanding of employees to the core value of ISTAWA at Lamongan Muhammadiyah Hospital. This survey conducted from August to November 2016 and involved 84 employees of Lamongan Muhammadiyah Hospital. Research instrument through questionnaire. Data analysis was done descriptively. This study shows that most (67%) of employees do not know the core value of ISTAWA. Information about the value obtained by employees from direct supervisors (76%), regular unit meetings (10%), SDI 7%, and Director (7%). Understanding the meaning to the value of ISTAWA from employees of Lamongan Muhammadiyah Hospital which is the highest lies in the aspect of sincerity. This research recommends that the management of Rumah Sakit Muhammadiyah Lamongan make socialization program and internalization of core value of ISTAWA to all employees so that the value can be an organizational culture that is implemented in every services to patient.